Substance P-modified human serum albumin nanoparticles loaded with paclitaxel for targeted therapy of glioma - Chunhui Ruan; Lisha Liu; Yifei Lu; Yu Zhang; Xi He; Xinli Chen; Yujie Zhang; Qinjun Chen; Qin Guo; Tao Sun; Chen Jiang (Elsevier, 2018)
The blood-brain barrier (BBB) and the poor ability of many drugs to cross that barrier greatly limits the efficacy of chemotherapies for glioblastoma multiforme (GBM). The present study exploits albumin as drug delivery vehicle to promote the chemotherapeutic efficacy of paclitaxel (PTX) by improving the stability and targeting efficiency of PTX/albumin nanoparticles (NPs). Here we characterize PTX-loaded human serum albumin (HSA) NPs stabilized with intramolecular disulfide bonds and modified with substance P (SP) peptide as the targeting ligand. The fabricated SP-HSA-PTX NPs exhibited satisfactory drug-loading content (7.89%) and entrapment efficiency (85.7%) with a spherical structure (about 150 nm) and zeta potential of −12.0 mV. The in vitro drug release from SP-HSA-PTX NPs occurred in a redox-responsive manner. Due to the targeting effect of the SP peptide, cellular uptake of SP-HSA-PTX NPs into brain capillary endothelial cells (BCECs) and U87 cells was greatly improved. The low IC50, prolonged survival period and the obvious pro-apoptotic effect shown by TUNEL analysis all demonstrated that the fabricated SP-HSA-PTX NPs showed a satisfactory anti-tumor effect and could serve as a novel strategy for GBM treatment.